THE IMPACT OF WORD CLOUDS ON STUDENTS' VOCABULARY ENHANCEMENT - FaqeAbdulla, Baraat Ismael (International Journal of English Learning and Applied Linguistics (IJELAL), 2024)
A strong vocabulary is essential for improved communication, which entails engaging with people in an effective manner. University freshmen always have a hard time learning a lot of new words related to their new academic lives. This problem can be resolved with the aid of Word Cloud, a language-related application. One Word Cloud is examined in the current study as a potential app to help students increase their vocabulary. The purpose of this study is to look into how Word Clouds affect students' ability to expand their vocabulary in English. The study hypothesizes that Word Clouds significantly influence students' vocabulary development. Not every student will find traditional vocabulary instruction methods to be interesting or useful. To assess the students' vocabulary growth, this experimental study compares the pre- and post-assessments of two groups of students before and after the treatment using the statistical T-Test. The findings indicate that Word Clouds have some effect on students' vocabulary, but not much because there was little variation in the post-test scores between the two groups. The study's conclusion aids in the advancement of language instruction and supports teachers in expanding their students' vocabulary.